2022
DOI: 10.3389/fnagi.2021.791532
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Brain and Cognition in de novo Parkinson's Disease

Abstract: Background and Objective: Brain atrophy and cognitive impairment in neurodegenerative diseases are influenced by sex. We aimed to investigate sex differences in brain atrophy and cognition in de novo Parkinson's disease (PD) patients.Methods: Clinical, neuropsychological and T1-weighted MRI data from 205 PD patients (127 males: 78 females) and 69 healthy controls (40 males: 29 females) were obtained from the PPMI dataset.Results: PD males had a greater motor and rapid eye movement sleep behavior disorder sympt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
26
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 41 publications
4
26
2
1
Order By: Relevance
“…Moreover, the sex difference was not considered a comparable factor in our meta-analysis, while Oltra et al (2022) reported that the sex effect may significantly affect cognitive impairment in patients with PD. 69 Sex differences may require attention in future studies of cognitive assessment in patients with PD.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Moreover, the sex difference was not considered a comparable factor in our meta-analysis, while Oltra et al (2022) reported that the sex effect may significantly affect cognitive impairment in patients with PD. 69 Sex differences may require attention in future studies of cognitive assessment in patients with PD.…”
Section: Discussionmentioning
confidence: 88%
“…Moreover, the sex difference was not considered a comparable factor in our meta-analysis, while Oltra et al (2022) reported that the sex effect may significantly affect cognitive impairment in patients with PD. 69 Sex differences may require attention in future studies of cognitive assessment in patients with PD. Meanwhile, some studies pointed out that other factors like diabetes mellitus could affect the progression of PD and its motor and non-motor symptoms, especially the cognition symptoms, 46 , 70 , 71 , 72 which may affect the efficacy of rTMS intervention and the result of this meta-analysis.…”
Section: Discussionmentioning
confidence: 99%
“…In the prodromal and dementia stages of LBD, patients show different sex predominance in core clinical features. Previous studies in patients with PD and PDD showed that RBD was more common in men [ 12 , 37 ], and its presence and severity were associated with decreased cerebrospinal fluid (CSF) alpha-synuclein level [ 38 , 39 ]. Although Yu et al [ 39 ] showed that omen had lower CSF alpha-synuclein levels (1429 ± 164 vs 1831 ± 60, p = 0.02) than men, and only one longitudinal study [ 40 ] revealed a significant correlation between estimated changes in alpha-synuclein level and RBD-SQ scores ( p = 0.001, data not available), we still do not know how sex influences occurrence of RBD by influencing alpha-synuclein levels.…”
Section: Discussionmentioning
confidence: 99%
“…Parkinson’s disease (PD) has a higher incidence in males than females with a ratio of 2:1 ( Oltra et al, 2022 ; Shulman and Bhat, 2006 ), and progression of degeneration of the nigrostriatal system is thought to be worse in men ( Jurado-Coronel et al, 2018 ). Men with PD have more severe cognitive impairment, namely executive function and processing speed as measured by the Montreal Cognitive Assessment and the Symbol Digits Modalities Test, respectively ( Oltra et al, 2022 ; Oltra et al, 2021 ; Reekes et al, 2020 ). Also, PD males have worse cortical thinning in postcentral and precentral regions and smaller volumes in thalamus, caudate, putamen, pallidum, hippocampus, and brainstem compared with PD females ( Oltra et al, 2022 ; Oltra et al, 2021 ).…”
Section: Sex Differences In the Brain During Health And Diseasementioning
confidence: 99%
“…Men with PD have more severe cognitive impairment, namely executive function and processing speed as measured by the Montreal Cognitive Assessment and the Symbol Digits Modalities Test, respectively ( Oltra et al, 2022 ; Oltra et al, 2021 ; Reekes et al, 2020 ). Also, PD males have worse cortical thinning in postcentral and precentral regions and smaller volumes in thalamus, caudate, putamen, pallidum, hippocampus, and brainstem compared with PD females ( Oltra et al, 2022 ; Oltra et al, 2021 ). Whether testosterone deficiency in aging males or exposure to pesticides that act via estrogen-blocking properties can predispose to PD is a subject of speculation ( Brenner, 2012 ; Okun et al, 2004 ; Okun et al, 2006 ; Okun et al, 2002 ).…”
Section: Sex Differences In the Brain During Health And Diseasementioning
confidence: 99%